Decentralized behavior-based formation control of multiple robots considering obstacle avoidance - Lee, Giroung; Chwa, Dongkyoung (Intelligent Service Robotics, 2018)
This paper proposes a decentralized behavior-based formation control algorithm for multiple robots considering obstacle avoidance. Using only the information of the relative position of a robot between neighboring robots and obstacles, the proposed algorithm achieves formation control based on a behavior-based algorithm. In addition, the robust formation is achieved by maintaining the distance and angle of each robot toward the leader robot without using information of the leader robot. To avoid the collisions with obstacles, the heading angles of all robots are determined by introducing the concept of an escape angle, which is related with three boundary layers between an obstacle and the robot. The layer on which the robot is located determines the start time of avoidance and escape angle; this, in turn, generates the escape path along which a robot can move toward the safe layer. In this way, the proposed method can significantly simplify the step of the information process. Finally, simulation results are provided to demonstrate the efficiency of the proposed algorithm.
Keywords: Behavior-based; Behavior-based methods; Escape angle; Formation control; Heading angles; Information process; Multiple robot; Relative positions; Behavior-based method; Decentralized formation control; Escape angle; Multiple robots; Obstacle avoidance